Mowat-Wilson Syndrome as a Differential Diagnosis in Patients with Congenital Heart Defects and Dysmorphic Facies - Pachajoa H; Gomez-Pineda E; Giraldo-Ocampo S; Lores J (Dove Medical Press, 2022)
Harry Pachajoa,1- 3 Eidith Gomez-Pineda,2 Sebastian Giraldo-Ocampo,4 Juliana Lores1- 3 1Genetics Division, Fundación Valle del Lili, Cali, Colombia; 2Centro de Investigaciones en Anomalías Congénitas y Enfermedades Raras (CIACER), Universidad Icesi, Cali, Colombia; 3Centro de Investigaciones Clínicas, Fundación Valle del Lili, Cali, Colombia; 4Universidad del Valle, Cali, ColombiaCorrespondence: Harry Pachajoa, Centro de Investigaciones en Anomalías Congénitas y Enfermedades Raras (CIACER), Universidad Icesi, Calle 18 No. 122-135 Pance, Cali, Colombia, Tel +57 5552334 ext 7653, Email hmpachajoa@icesi.edu.coAbstract: Mowat-Wilson syndrome is a rare, autosomal dominant neurodevelopmental disorder characterized by distinctive facial gestalt and intellectual disability that is often associated with microcephaly, seizures and multiple congenital anomalies, mainly heart defects. More than 350 patients and 180 genetic variants in the ZEB2 gene, have been reported with an estimated frequency of 1 per 70,000 births. Here we report a Colombian female patient with facial gestalt, intellectual disability, microcephaly, congenital heart defects, hypothyroidism and middle ear defect associated with the nonsense pathogenic variant c.2761C>T (p.Arg921Ter) in the ZEB2 gene. This case contributes to the understanding of the clinical complications and the natural history of this complex and clinically heterogeneous disorder but also to the awareness that patients with heart congenital defects and dysmorphic facies may present an underlying genetic disorder.Keywords: neurodevelopmental disorder, ZEB2, genetic disorder, multiple congenital disorder